1981
DOI: 10.1159/000212472
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation and Oxaloacetate Inhibition of Hepatic Respiratory Metabolism in Male Garden Lizards of Three different Age-Groups

Abstract: Thermal inactivation of hepatic succinic dehydrogenase (SDH) (EC 1.3.99.1) at 51 ± 1 °C resulted in a higher degree of inhibition in middle-aged and old than in young lizards. The oxaloacetate inhibition of SDH activity and that of oxygen uptake of liver homogenates after 1 h of incubation also showed a similar pattern of age dependency. With increase in time interval (from 15 to 60 min) the young and to some extent the middle-aged lizards showed a partial recovery from inhibition of oxygen consumption of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This partially confirms the prediction of Baird et al [23] that the thermolability of rat liver catalase remains unaltered in senescent animals. Taken together, these observations along with those of others (muscle lactate dehydrogenase [24], parotid a-amylase [25] and G6PDH [26]) are in contrast to Orgel's [5] proposition that senescence results from progressive accumulation of altered protein molecules with passage of time [23], Since previous observations from our labo ratory indicated that the thermolability at 51 ± 1 °C of hepatic succinic dehydrogenase [27] and G6PDH in liver and kidney of garden lizard [11] increased with age in sup port of Orgel's [5] predictions and the present result in catalase contradicts the hypothesis, it is possible that during senescence an accumu lation of altered representatives occur in some proteins and not in others even though the mechanism of such selective change is still unclear. Therefore, we support the view that the general applicability of Orgel's [5] error catastrophe hypothesis needs re-evaluation as suggested earlier [28,29] to explain the devia tions about which Orgel [30] himself was aware of.…”
Section: Discussionmentioning
confidence: 44%
“…This partially confirms the prediction of Baird et al [23] that the thermolability of rat liver catalase remains unaltered in senescent animals. Taken together, these observations along with those of others (muscle lactate dehydrogenase [24], parotid a-amylase [25] and G6PDH [26]) are in contrast to Orgel's [5] proposition that senescence results from progressive accumulation of altered protein molecules with passage of time [23], Since previous observations from our labo ratory indicated that the thermolability at 51 ± 1 °C of hepatic succinic dehydrogenase [27] and G6PDH in liver and kidney of garden lizard [11] increased with age in sup port of Orgel's [5] predictions and the present result in catalase contradicts the hypothesis, it is possible that during senescence an accumu lation of altered representatives occur in some proteins and not in others even though the mechanism of such selective change is still unclear. Therefore, we support the view that the general applicability of Orgel's [5] error catastrophe hypothesis needs re-evaluation as suggested earlier [28,29] to explain the devia tions about which Orgel [30] himself was aware of.…”
Section: Discussionmentioning
confidence: 44%
“…Estimation of thermo stability of enzymes is one such method. Thermolability at 51 ± 1°C of hepatic SDH [99] and G6PDH in liver and kidneys of gar den lizards [100] increased during ageing (ta ble 12) in support of Orgel's [97] predictions of accumulation of altered enzyme molecules with advancing age. The results are compara ble with the findings on G6PDH in various tissues of C57BL/6J mice during ageing [88], On the other hand, the hepatic catalase maintained resistance against thermal inacti vation at 60 ± 1 °C throughout the life-span, suggesting minimal alteration in enzyme mol ecules [86].…”
Section: Characteristics O F Certain Proteinsmentioning
confidence: 62%
“…In contrast, in the heart, the inhibition of SDH by oxalo-acetate declined with age [37,99,103]. /vChlorophenoxy acetic acid, an allosteric inhibitor [104], caused a higher degree of inhibition of hepatic SDH activity in middle-aged and old lizards than in young counterparts [81].…”
Section: Characteristics O F Certain Proteinsmentioning
confidence: 99%
“…The significance of basic age changes in hepatic SDH activity from young to old through middle-aged lizards has already been referred lo in earlier publications Patnaik, 1981 .Kara andPatnaik, 1985]. This aspect has not been discussed again to avoid repetition.…”
Section: Resultsmentioning
confidence: 99%